Psychological Effects of Domestic Violence Against Women - Zancan, Natália; Wassermann, Virginia Graciela (Revista de Psicologia da IMED, 2013)
Domestic violence is considered a human rights violation and a public health issue. In its most common form is committed by intimate partner, in which is revealed the men’s dominant behavior exercised over women in the privacy of the home and can cause serious problems in women’s life quality. Considering the complexity of the problem, this research aims to identify the psychological and socio-demographic characteristics of four women located at Casa de Apoio à Mulher Vítima da Violência in the State of Rio Grande do Sul. In accordance with qualitative methodological approach, it was a study of multiple cases using the following instruments: a personal and socio-demographic data sheet, Beck Scales, Rosenberg’s Self-Esteem Scale and Rorschach Method (CS). The women in the research show signs of low self-esteem, clinical anxiety and depression, lack of ability to enter relationships, difficulties facing the stresses of everyday life, and difficulties to express their feelings.